Hubungan Tingkat Stress Dengan Kejadian Dismenore Pada Remaja Putri Di SMAN 1 Kota Bengkulu Tahun 2025 - Suci Rohima Janista; Emi Pebriani; Danur Azissah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Dysmenorrhea is menstrual pain frequently experienced by adolescent girls and impacts concentration, school attendance, and quality of life. One psychological factor contributing to dysmenorrhea is stress levels. Stress can affect reproductive hormone balance, thereby worsening menstrual pain. This study aimed to determine the relationship between stress levels and dysmenorrhea among adolescent girls at SMAN 1 Bengkulu City in 2025. This study used quantitative analytical methods with a cross-sectional design. Data were collected by distributing questionnaires to 80 respondents, all female adolescents in grades 10 and 11 at SMAN 1 Bengkulu City. The sampling technique used purposive sampling. Data were analyzed using univariate and bivariate methods using the Chi-Square test.. The results showed that almost all respondents experienced moderate stress (37.5%) and moderate dysmenorrhea (36.3%). The results of the Chi-Square test obtained a p-value (0.022) smaller than the ∝ value (0.05), so H0 is rejected and Ha is accepted, which means that statistically there is a significant relationship between stress levels and the incidence of dysmenorrhea in adolescent girls at DMAN 1 Bengkulu City in 2025.. Based on the results of the study, it is recommended that schools and health workers provide education on stress management and reproductive health as an effort to prevent and treat dysmenorrhea in adolescent girls.